Novel coronaviruses and astroviruses in bats - Chu, Daniel K. W. (Virol Sin, 2009)
Zoonotic transmissions of emerging pathogens from wildlife to human have shaped the history of mankind. These events have also highlighted our poor understanding of microorganisms circulated in wild animals. Coronaviruses and astroviruses, which can be found from a wide range of mammals, were recently detected in bats. Strikingly, these bat viruses are genetically highly diverse and these interesting findings might help to better understand the evolution and ecology of these viruses. The discoveries of these novel bats viruses not only suggested that bats are important hosts for these virus families, but also reiterated the role of bats as a reservoir of viruses that might pose a zoonotic threat to human health.